Effect of pre-treatments on desirable qualities attributes of watermelon rind based candy - Nasir, Hina; Allai, Farhana; Gull, Amir; Ganaie, Tariq Ahmad; Azad, Z R A (Journal of Postharvest Technology, 2020)
The present study investigated the influence of different treatments on various desirable quality attributes of watermelon rind based candy. Four different samples of candy were prepared by using different levels of citric acid and pectin in the ratio of 0%, 1:1%, 1:1.5%, 1.5:1.5% respectively. Then packed in LDPE pouches and stored under ambient conditions for about two months. Results showed increase in acidity from 0.30-0.64%, ascorbic acid content 4.11-4.59, reducing sugar 29.64-34.96%, L* value 41.86-53.80, a* value 1.51-2.74 and hardness 79-96N with increase in concentration of citric acid and pectin respectively. While as pH value decreased from 5.74-5.25, TSS from 76.14-68.05, aw from 0.732-0.697 respectively. From the present study it can be concluded that watermelon rind based candy supplemented with 1.5% pectin and 1.5% citric acid was found to have an excellent quality characteristics compared to control samples. Further it can be concluded that drying period of 18 hr was found most appropriate for drying watermelon rind based candy.